Corrosion protection by novel conversion coatings on structural AI 6061 (2022)
Chromate conversion coatings have witnessed limited acceptability in recent times. The coatings contain Cr (VI) species that have been classified as environmental hazards and injurious to human. Thus, the use of environment-friendly and non-carcinigenic novel inorganic- inorganic hybrid conversion coatings are being explored. Vanadate (VCC), hybrid Vanadate/Molydate (HCC) conversion coatings on A16061 have been classified in terms of corrosion and adhesion performance with reference to the untreated alloy. Natural exposure tests in the atmosphere and stanant near-neutral 3.5% sodium chloride solution, as well as patentio-dynamic polarization measurements showed that the corrosion rate for HCC is lower for Vanadate, which in turn outclassed the ‘bare’ alloy. However, clusters of passive incipient pits were revealed on the former after 120 h of exposure in stagnant chloride solution. Both conversion coatings outperformed the untreated aluminiun alloy after atmospheric corrosion and adhesion tests.